2010
DOI: 10.1002/ibd.21175
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the novel ST2/IL-33 system in patients with inflammatory bowel disease

Abstract: The novel association between the ST2/IL-33 system and IBD seems to identify that variations in this axis might regulate the inflammatory process in these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
231
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 205 publications
(252 citation statements)
references
References 37 publications
20
231
1
Order By: Relevance
“…In the tumor stroma IL-33 immunoreactivity can also be identified in microvessels and myfibroblasts, this observation is consistent with previous findings from studies in patients with ulcerative colitis (30,(43)(44)(45). In those studies, IL-33 immunoreactivity was observed in both the inflamed colonic epithelium and lamina propria.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the tumor stroma IL-33 immunoreactivity can also be identified in microvessels and myfibroblasts, this observation is consistent with previous findings from studies in patients with ulcerative colitis (30,(43)(44)(45). In those studies, IL-33 immunoreactivity was observed in both the inflamed colonic epithelium and lamina propria.…”
Section: Discussionsupporting
confidence: 92%
“…In the investigation of IL-33 in colonic diseases, it has been found that the increase of IL-33 is related to the development of colorectal chronic inflammation (ulcerative colitis) (29,30), whereas the epidemiological studies from different countries have revealed that ulcerative colitis may significantly raise the CRC risk (33)(34)(35)(36)(37)(38)(39). Our current study, in our best knowledge, is the first study to demonstrate a dynamic change of IL-33 from the colorectal adenomas to the sporadic CRCs.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Robust data indicate that IL-33 expression is increased in the inflamed mucosa of IBD patients versus healthy controls, particularly in UC [Beltran et al 2010;Kobori et al 2010;Pastorelli et al 2010;Seidelin et al 2010]. Mucosal expression of IL-33 is mostly localized to nonhematopoietic cells, particularly intestinal epithelial cells [Beltran et al 2010; Pastorelli et al 2010; Seidelin et al 2010] and myofibroblasts [Kobori et al 2010] (Figures 2A and C).…”
Section: Introductionmentioning
confidence: 92%
“…Less was known regarding the importance of this cytokine in the maintenance of intestinal homeostasis and its potential role in gut-associated diseases. However, in 2010, four independent groups reported the association of IL-33 with IBD, with elevated expression specifically in UC patients [Beltran et al 2010;Kobori et al 2010;Pastorelli et al 2010;Seidelin et al 2010]. Although emerging data is beginning to uncover the precise function of IL-33 in the gastrointestinal (GI) tract, little has been established that mechanistically addresses the role of IL-33 during normal gut homeostasis as well as during IBD.…”
Section: Introductionmentioning
confidence: 99%